2021
DOI: 10.1542/hpeds.2020-001990
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Faculty and Trainee Attitudes Toward the COVID-19 Pandemic

Abstract: OBJECTIVES: The coronavirus disease 2019 (COVID-19) pandemic is an unprecedented event in modern medicine. In this study, we evaluate pediatric faculty and trainee attitudes and perspectives related to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and their roles in the COVID-19 pandemic. METHODS: We surveyed a pediatric hospital’s faculty and trainees (n = 701) in April 2020 about their concerns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…One-half of respondents reported being excluded from the care of patients with suspected or confirmed COVID-19, but the vast majority did not believe they should be excluded from either, suggesting that residents without health concerns should be included in the care of patients with COVID-19 going forward. This is consistent with the findings of Kazmerski et al, 21 who found that the majority of residents believed trainees were essential personnel and should participate in direct patient care during the pandemic.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One-half of respondents reported being excluded from the care of patients with suspected or confirmed COVID-19, but the vast majority did not believe they should be excluded from either, suggesting that residents without health concerns should be included in the care of patients with COVID-19 going forward. This is consistent with the findings of Kazmerski et al, 21 who found that the majority of residents believed trainees were essential personnel and should participate in direct patient care during the pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, this is one of the first studies in which researchers examine the impact of COVID-19 on training from the perspectives of pediatric residents. 21 At the onset of the pandemic and in the face of overwhelming uncertainty about the future, residency program leaders were forced to rapidly adjust resident schedules and training experiences. 11,12 This resulted in significant changes to respondents' clinical experiences including canceled clinics and clinical electives, fewer inpatient shifts, and added jeopardy rotations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, graduating medical students entered a residency training environment significantly disrupted by the COVID-19 pandemic [14]. Lastly, many trainees had concerns about their personal risk of COVID-19 infection [15], especially at the onset of the pandemic when information about COVID-19 was still evolving.…”
Section: Introductionmentioning
confidence: 99%
“…An impression of lack of support or a sense of not being recognized can widen the rift between staff and their leaders and institutions, triggering further distress and impacting well‐being 11,37,38 . Effective communication has the power to reduce stress and increase trust in leadership, 39,40 including in oncology 13 . Instilling a sense of solidarity and teamwork, with increased visibility of leaders working alongside staff, can help raise morale and improve well‐being 40 …”
Section: Discussionmentioning
confidence: 99%